2019
DOI: 10.1093/pasj/psz047
|View full text |Cite
|
Sign up to set email alerts
|

Extended star-forming regions within galaxies in a dense proto-cluster core at z = 2.53

Abstract: At z ∼ 2, star-formation activity is thought to be high even in high-density environments such as galaxy clusters and proto-clusters. One of the critical but outstanding issues is if structural growth of star-forming galaxies can differ depending on their surrounding environments. In order to investigate how galaxies grow their structures and what physical processes are involved in the evolution of galaxies, one requires spatially resolved images of not only stellar components but also star-forming regions wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 87 publications
0
8
2
Order By: Relevance
“…The compact dust emission in our ALMA sample appears to be inconsistent with previous results that showed that the Hα emission is more extended than the stellar continuum emission in less massive, less dusty SFGs at z∼2 (Suzuki et al 2019;Wilman et al 2020). Note that our targets are all massive SFGs with >…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The compact dust emission in our ALMA sample appears to be inconsistent with previous results that showed that the Hα emission is more extended than the stellar continuum emission in less massive, less dusty SFGs at z∼2 (Suzuki et al 2019;Wilman et al 2020). Note that our targets are all massive SFGs with >…”
Section: Discussioncontrasting
confidence: 99%
“…The centrally rising sSFR profiles seem to be at odds with previous studies that have applied dust gradient corrections to translate Hα profiles to SFR profiles, finding that dustcorrected sSFR profiles are centrally dipping in massive SFGs at z∼2 (Tacchella et al 2015(Tacchella et al , 2018Suzuki et al 2019). This difference may be due to underestimates of the central dust extinction and/or the different sample selection.…”
Section: Spatially Resolved Stellar Mass and Sfrcontrasting
confidence: 75%
See 1 more Smart Citation
“…These inverse gradients are contrary to what is observed in the majority of both SF and Q galaxies: there is in fact overwhelming evidence that most galaxies form in an inside-out fashion. Firstly, by comparing the size of the star-forming gas disc to the size of the stellar disc, the instantaneous radial growth rate of SF galaxies has been shown to be positive (Pezzulli et al 2015;Wang et al 2019;Nelson et al 2016;Paulino-Afonso et al 2017;Suzuki et al 2019). Secondly, the stellar populations of most SF and Q galaxies have negative age gradients with radius (e.g.…”
mentioning
confidence: 99%
“…Moreover, they have shown that the difference of the light profiles has become larger with increasing stellar mass. Also at z > 2, Suzuki et al (2019) have revealed extended Hα profiles with AO-assisted imaging data. These results indicate at a fixed aperture size one potentially might miss Hα flux at large radii.…”
Section: Hα Luminosity Functionmentioning
confidence: 85%